The Overview of Japanese Encephalitis and Nipah Diseases - Indrawati Sendow (Indonesian Center for Animal Research and Development, 2000)
An outbreak of encephalitis in Malaysia, caused a panic among Veterinary and animal husbandry expert internationally in late 1998. Suspected Japanese encephalitis (JE) had been eliminated after an intensif investigation to diagnose the outbreak. The result indicated that Nipah virus played an important role caused the outbreak. Controversion on causative agent between JE and Nipah leads to further discussion on the difference and similarities between JE and Nipah from different aspects included their aetiology, clinical signs, host, diagnosis and control the disease. Keywords: Japanese encephalitis, nipah